Understanding China's strategic culture: a clash of realpolitik and cultural moralism - Lee, Jonghyuk (2023)
China’s foreign policies are shaped by two distinct political cultures: the authoritarian culture of communist ideology and the cultural moralism based on Confucianism. While these values are interwoven in China’s strategic culture, their manifestation varies among different schools of thought. Understanding these differences provides fresh insights into ongoing discussions on China’s ability to serve as a responsible global superpower. Although Western and Chinese perspectives on China’s strategic culture differ significantly, it is essential to consider nuanced views that differentiate between various leaders in China.